Melia dubia : An ideal tree for commercial agroforestry - Kumar, Sushil; Yadav, Ashok; Arunachalam, Ayyandar (Indian Farming, 2022)
Agroforestry or trees outside forests are vital for ensuring environmental resilience in terrestriallandscapes. In this regard, growing trees on farmlands i.e. agroforestry ensures livelihood securityto the farming communities. Nonetheless, there are a few bottlenecks in the farmers’ adoptionprocess of agroforestry trees as they ought to be fast-growing, deciduous straight bole, highmarket value, assured buyback, and low maintenance cost, etc. On these counts, and based on treeideotypes for agroforestry, Melia dubia has both structural and functional traits for agroforestry,and essentially has market value as well. This study thus demonstrates various benefits of Meliadubia due to which it is gaining interest among the farmers and emerging as a sustainable andpromising raw material for commercial agroforestry.